Accounting manipulations related to financial assets - Kutera, Małgorzata (Management Sciences, 2018)
The main purpose of this paper is to present the types and consequences of accounting manipulations concerning financial assets, mainly in the context of their impact on the financial results presented by enterprises. The research methodology is based on a critical analysis of the current legal solutions and case studies. Three different entities audited by the author have been selected to illustrate the most frequently used techniques of accounting manipulations. These relate to the pricing and presentation of blocks of shares listed on the stock exchange as well as shares not traded on a regulated market in the financial statements. The research results unambiguously confirm that the current wording of the provisions of the accounting balance sheet law in this regard leave a rather large degree of freedom in their interpretation. Qualified accountants skilfully use these legal gaps to a significant extent to paint a better picture of the enterprise
Management Sciences, 2018, vol. 23, no. 3, s. 23-29
Keywords: accounting manipulations; creative accounting; financial assets; share pricing; manipulacje księgowe; rachunkowość kreatywna; aktywa finansowe; wycena udziałów i akcji